Free-riding in alliances: Testing an old theory with a new method. (July 2015) - Plümper, Thomas; Neumayer, Eric
We revisit the old and well-established theory of free-riding in military alliances. Existing empirical evidence infers free-riding from the larger military expenditures per gross domestic product (GDP) of countries of larger GDP. Yet, larger countries have broader military and geostrategic interests that result in larger defense burdens, thus creating an identification problem for existing tests of free-riding behavior. We therefore develop alternative predictions that ignore differences in the level of military spending and instead relate to growth in spending over time. The safety level of smaller members of an alliance is affected, simultaneously, by changes to military spending of the largest alliance member as well as by spending changes of the main enemy. Using the North Atlantic Treaty Organization (NATO) as test case, we estimate country-specific response functions of the smaller alliance members to growth in US military spending on the one hand and to growth of Soviet spending (if in excess of US growth) on the other, covering the period 1956–1988. Results from our quasi-spatial approach corroborate one part of the theory in that we find the vast majority of the smaller NATO allies to be free-riders. However, our empirical evidence flatly contradicts the other part of the free-riding theory: the extent of free-riding is not a function of country size. Smaller allies free-ride, but the relatively larger of the smaller allies do not free-ride any less than the relatively even smaller alliance partners.